Combined effects of cryogenic temperature and strain rates on compressive behavior of concrete. (September 2022) - Jin, Liu; Liu, Kaixin; Zhang, Renbo; Yu, Wenxuan; Du, Xiuli; Deng, Xiaofang
Concrete structures in extremely cryogenic environments may be subject to dynamic loadings as a result of occasional accidents or terrorist attacks during the service life. Considering the cryogenic temperature effect and strain rate effect of each phase for concrete, a meso-scale numerical model of the concrete subjected to cryogenic temperature and dynamic loadings was presented in this study, which serves as a preliminary foundation for calculating and evaluating the performances of concrete structures at cryogenic temperature. Taking concrete cube as an example, the dynamic compressive behavior and strain rate effect of concrete specimens at cryogenic temperature from 20 °C to –160 °C were modelled and investigated. The numerical results indicate that the failure appearances and compressive strength are highly related to the cryogenic temperature and dynamic loadings. The compressive strength at cryogenic temperature is greater than that at ambient temperature, and the sensitivity of dynamic compressive strength to strain rate is enhanced at cryogenic temperature. Moreover, the absorbed energy and dynamic elastic modulus tend to increase with the decrease of temperature and increase of strain rate. According to the numerical results, an empirical formula on dynamic increase factor of compressive strength at cryogenic temperatures (CDIF T ) was established.